An Easy Framework to Organize Complex Data - Feuerbach, Ann (Vilnius University Open Series, 2025)
The holistic and multidimensional nature of anthropological research results in an enormous amount of data, but the problem is how to organize it in such a way as to be useful for identifying complex patterns across different fields. This paper proposes a basic Framework for organizing metadata into categories: Space (where), Time (when), Matter (who and what), and Energy (how), and then separates these into two categories: empirical data and ideational data. This method reduces preconceptions by separating out the tangible evidence from the intangible and allows evidence to be understood and tested from different perspectives.